Assertive Behavior of Women Leaders Create Excellent Performance: case study at Pondok Pesantren Al Husna Al Alawi Senori Tuban - Siti Fatimah; Siti Nurrohmah (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Women's leadership has now become a public conversation. Various controversies about women's leadership began to emerge. Even among the fuqoha 'to the Islamic philosophers also debate about the law of women's leadership. This assertive behavior was also found in the head of Pesantren Al-Husna Al-Alawi. This is descriptive qualitative research in which all data and findings will be presented in descriptive form. Sources of data researchers get through the process of interviews, observation, and documentation. The results showed that the head of Pesantren Al-Husna Al-Alawi Putri had assertive behavior, which with this assertive behavior made the performance of the board increase. This assertive behavior can be seen from how to lead, communicate, coordinate, provide direction, to give warnings and motivation to all members of the board. Efforts made by the head of Pesantren Al-Husna Al-Alawi Putri in creating superior performance include education and training, incentives, motivation, and the creation of a clean and comfortable learning environment